2018
DOI: 10.1371/journal.pone.0201008
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation, cognitive reserve, and cognition in healthy older people

Abstract: There is evidence to suggest that social isolation is associated with poor cognitive health, although findings are contradictory. One reason for inconsistency in reported findings may be a lack of consideration of underlying mechanisms that could influence this relationship. Cognitive reserve is a theoretical concept that may account for the role of social isolation and its association with cognitive outcomes in later life. Therefore, we aimed to examine the relationship between social isolation and cognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
150
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(166 citation statements)
references
References 42 publications
3
150
1
12
Order By: Relevance
“…In spite of this, whether or not bilingualism confers any benefit in age-related disorders remains a hotly debated topic. On the one hand, the linguistic profile of a bilingual, i.e language proficiency (Bialystok & Feng, 2009;Xie, 2018) and usage (de Bruin, 2020), as well as other cognitive reserve factors, i.e.-social activity (Evans et al, 2018;Scarmeas & Stern, 2003) and occupation (Darwish, Farran, Assaad, & Chaaya, 2018), might act to highlight or, conversely, mask such a bilingual advantage. On the other hand, the incomplete understanding of what drives the effect (if any) (Bak, 2016) makes it more difficult to define the outcome measures and thus increases the probability of false conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this, whether or not bilingualism confers any benefit in age-related disorders remains a hotly debated topic. On the one hand, the linguistic profile of a bilingual, i.e language proficiency (Bialystok & Feng, 2009;Xie, 2018) and usage (de Bruin, 2020), as well as other cognitive reserve factors, i.e.-social activity (Evans et al, 2018;Scarmeas & Stern, 2003) and occupation (Darwish, Farran, Assaad, & Chaaya, 2018), might act to highlight or, conversely, mask such a bilingual advantage. On the other hand, the incomplete understanding of what drives the effect (if any) (Bak, 2016) makes it more difficult to define the outcome measures and thus increases the probability of false conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…4 An association between social isolation and cognitive functioning has been demonstrated by recent cross-sectional 5 and longitudinal studies. 6,7 For example, it has been shown that social isolation is related to decreased cognitive function based on data from a A recent systematic review on the longitudinal association between social isolation and cognitive functioning showed that these factors are weakly associated. 8 However, most of these longitudinal studies focused on social network and social activities without using standardized instruments (eg, using living alone as a surrogate for social isolation).…”
Section: Introductionmentioning
confidence: 99%
“…When data are disaggregated by sex, husbands who are caregivers are at greater risk for developing dementia than caregiving wives, suggesting that women may effectively find protection in other social ties or an earlier history of social support, while men may not find such ties outside of their marriage (e.g., Dykstra & Gierveld, 2014). Theoretically, since women are more likely to seek social support than men (Billings and Moos, 1981;Folkman and Lazarus, 1980;Hamilton and Fagot, 1988;Stone and Neale, 1984) one would think that social support would be a larger contributor to women's cognitive reserve (Evans et al, 2018). However, based on the dearth of studies in women, further research examining sex differences in social support are required to understand how different kinds of social support would mitigate against AD pathology.…”
Section: Social Supportmentioning
confidence: 99%